Clinical Features and Early Recognition of 242 Cases of Autoimmune Encephalitis - Yang, Mu; Lian, Yajun (Frontiers in Neurology, 2022)
Abstract Objective: To analyze the clinical features of common autoimmune encephalitis and evaluate the sensitivity of antibodies contributing to epilepsy signs and symptoms(ACES) score. Methods: Collecting and analyzing the data of 242 AE patients diagnosed in the First Affiliated Hospital of Zhengzhou University from August 2015 to December 2020 in this retrospective study. The 6 items of the ACES score (cognitive symptoms, behavioral changes, autonomic symptoms, speech problems, autoimmune diseases, temporal magnetic resonance imaging hyperintensities) were screened in patients with complete clinical data. Results: (1)242 patients were included, with 147 cases of anti-N-methyl-D-aspartate receptor encephalitis and anti-γ-aminobutyric acid type B receptor antibody encephalitis 47 cases, 48 cases of anti-leucine-rich glioma inactivating protein 1 antibody encephalitis. The most common clinical symptoms are cognitive impairment (77%), behavior changes (79%), and seizures (71%). 129 cases (54%) combined with autonomic dysfunction, such as gastrointestinal dysmotility, sinus tachycardia, and central hypoventilation. 12 cases had autoimmune diseases, most of which were thyroid diseases. (2) 127 patients with complete clinical data evaluated ACES score, 126 cases of whom (126/127, 99.2%) equal to or great than 2 point, 1 case (1/127, 0.8%) less than 2 points. Interpretation: (1) Cognitive impairment, abnormal behavior, and seizures are most common manifestations of AE, as well as autonomic symptoms. Thyroid disease is the most autoimmune disease in AE. Clinically, for patients of suspected AE, increasing the knowledge and testing of thyroid function and rheumatism is necessary. (2) ACES score is a simple, effective and easy-to-operate score, which has certain screening value for most patients suspected of AE.